Detection and identification of the large, exotic, crassostreine oyster Magallana bilineata (Röding, 1798) in northern Queensland, Australia. (2nd January 2021) - Willan, Richard C.; Nenadic, Nikolina; Ramage, Anita; McDougall, Carmel
ABSTRACT: Between September 2019 and February 2020, four separate discoveries of populations of a large rock oyster in the wild (albeit in anthropogenically modified habitats) in northern Queensland prompted a molecular and morphological investigation to determine the identity of the species. Sequencing of partial mitochondrial 16S, mitochondrial cytochrome oxidase I, and histone H3 genes of specimens from four sites spanning some 170 km demonstrates that their sequences match those for Magallana bilineata (Röding, 1798), a species not previously recorded from Australia. Given its large size and onshore habitat, it is most likely that M. bilineata is exotic to Australia and has been introduced recently; however its origin is difficult to ascertain because it is widespread (both naturally and through translocation for aquaculture) in the tropical Indo-Pacific Ocean. Given that, as with any non-native invading marine species, M. bilineata is deemed to be 'Prohibited Matter' under the Queensland Biosecurity Act 2014, it is being monitored by Biosecurity Queensland to determine if the establishment is permanent and if intervention by biosecurity agencies is feasible or would be effective.